Group Classification of a Generalized Lane-Emden System - Ben Muatjetjeja; Chaudry Masood Khalique; Fazal Mahmood Mahomed (Journal of Applied Mathematics)
We perform the group classification of the generalized Lane-Emden system xu′′+nu′+xHv=0,  xv′′+nv′+xgu=0, which occurs in many applications of physical phenomena such as pattern formation, population evolution, and chemical reactions. We obtain four cases depending on the values of n.